THE SETTLEMENT OF STREN–KALI WONOKROMO–SURABAYA: The City Image Based on the Development of Marginal Society - Paulus Bawole (Dimensi: Journal of Architecture and Built Environment, 2009)
As human beings the poor people in informal settlements also have the right to live better like any other well-off people. Although the government regards them as illegal, they demonstrate great ingenuity in developing their residential neighborhoods. Public spaces are the living room for the people living in the informal settlements - the place where people come to enjoy their settlement. The strategy of sustainable development for informal settlements can be carried out well if the inhabitants are involved at the whole development process. In 2006 the population of Surabaya city was 2,716,971 people. An experience about urban upgrading in informal settlement along Wonokromo riverbank, Surabaya shows how the program implemented can improve the living quality of the inhabitants. With the program of Community Total Participation, the physical problems of the settlements can be reduced gradually. This paper will discuss the action research which tries to involve the inhabitants through total participatory strategy. The qualitative and quantitative data will be analyzed in order to find conclusions and to recommend alternative solutions.